Penggunaan Teknologi Perontokan untuk Menekan Susut dan Mempertahankan Kualitas Gabah - Rokhani Hasbullah; Riska Indaryani (PERTETA, 2009)
Paddy (Oryza sativa) is a plant producing rice as a staple food of Indonesian people. Efforts to increaserice production is done not only through the extention of the rice areas, but also to minimize postharvestlosses. This study aims to assess the use of thresher technology on postharvest losses of paddy. Threshingof paddy is done by three methods: (1) manually or “gebot”, (2) using pedal threshers, and (3) using powerthreshers. The results showed that the use of power thresher able to reduce paddy losses from 3,31 to4,35 % (for manual threshing or gebot) to be 0,49 to 1,21 %. The use of power thresher also reduces thepercentage of grain cracking from 7,1 % to be 4,1 % by threshing manually. Threshing capacity using powerthresher from 708.0 to 773.0 kg/h, while using the pedal thresher 84.96 to 113.00 kg/h and manual thresherresulting only 54.69 to 62.22 kg/h.Keywords: paddy, power thresher, pedal thresher, manual thresher, postharvest lossesDiterima: 15 Juni 2009; Disetujui: 29 September 2009